Computational design of immunogenic peptide constructs comprising multiple human leukocyte antigen restricted dengue virus envelope epitopes. Issue 9 (20th May 2022) - Kaushal, Neha; Jain, Sahil; Baranwal, Manoj
Abstract: Dengue virus (DENV) is endemic in 100 countries with the ability to impact nearly 50% of world population. DENV envelope (E) protein is responsible for viral attachment to host cells and has been target of various countermeasure development efforts. The current study focuses on a consensus computational approach to identify cross‐reactive, immunogenic DENV‐2 E peptides displaying promiscuity with a wide array of human leukocyte antigen (HLA) molecules. Four conserved peptides (FP‐1, FP‐2, FP‐3 and FP‐4) containing multiple CD8 + and CD4 + T cell epitopes were identified by employment of various immunoinformatics tools. FP‐1, FP‐2, FP‐3 and FP‐4 were estimated to bind with 227, 1787, 1008 and 834 HLA alleles, respectively. Root mean square deviation (RMSD) values obtained by molecular docking (CABS‐Dock) with 20 HLA alleles (10 each of HLA classes I and II) resulted into comparable RMSD values of identified epitopes with native peptides, which represents the natural presentation of epitopes to HLA molecules. These peptides were also found to be part of previous experimentally validated immunogenic peptides. Further, a dengue immunogenic peptide construct was generated by linking the four peptides, an adjuvant and a 6× histidine tag. The construct showed strong binding and stability with Toll‐like receptor. Collectively, these results provide strong evidence in the support of the immunogenic potential of the dengue immunogenic peptide construct. Abstract : Brief schematic representation of computational study of immunogenic peptide construct of dengue virus envelope epitopes.